(untitled) (Annals of Medical Research, 2022)
Aim: This study aimed to review the health anxiety and world assumptions of individuals and health care professionals concerning COVID-19 as well as the factors affecting there too. Materials and Methods: This study is descriptive, cross-sectional, and correlational. The "Personal Information Form (PIF)," "Health Anxiety Inventory (HAI)," and "World Assumptions Scale (WAS)" were used to collect data. Results: 56.6% of the participants were health care professionals. WAS total score differs based on gender, marital status, and educational background criteria (p<0.05). HAI score differs based on gender, the willingness to visit dining and shopping venues after the pandemic ends, house cleaning, social distancing, and the perception of the world’s change after the COVID-19 pandemic (p<0.05). Mean HAI scores of individuals from the society and health care professionals were found to as 16.42 ± 6.21 and 15.96 ± 6.37 respectively. Mean WAS scores of individuals from the society and health care professionals were found to as 107.40 ± 22.15 and 109.27 ± 19.84 respectively. A statistically significant relationship was determined between HAI and luck (fortune), self-worth, and WAS total scores (p<0.05). The linear regression model, established to examine the effect of demographic characteristics on the WAS score, was discovered to have statistical significance (F=4.180; p<0.001). The linear regression models were established to examine the effect of demographic characteristics on the HAI score (F=6.458, p<0.001), and the effect of WAS sub-dimension scores on anxiety (F=3.399; p=0.003) were both found to be statistically significant. Accordingly, the anxiety score decreases by 0.327 as the self-worth score increases by one unit (p=0.001). Conclusion: The anxiety experienced by health care workers and persons from society, as well as their world assumptions, are similar, according to this study, which was done near the end of the COVID-19 outbreak. However, it has been determined that the epidemic causes differences concerning perceptions about daily life and the well-being of the world.